THE MODERATING ROLE OF RELIGIOSITY ON ETHICAL BEHAVIORAL INTENTION: PLANNED BEHAVIORAL THEORY APPROACH - Rizki Amalia Elfita; Salsabila Hana Haninda (UNUSA Press, 2022)
The study aims to examine the influence of perceived behavioral control on ethical behavioral intention and examine the moderating role of religiosity on the relationship between perceived behavioral control and ethical behavioral intention. This is quantitative research by adding discussing explanations. Data were obtained from 110 questionnaires distributed to auditors in public accounting firms located in Surabaya. The statistical analysis used is Partial Least Square (PLS). The results of the study indicate that perceived behavioral control positively affects the ethical behavioral intention of auditors. Moreover, the results of the study show that religiosity has an influence on ethical behavioral intention, but it does not moderate the auditor’s perception of behavioral control.